Optimizing the Therapeutic Window of Targeted Drugs in Oncology: Potency‐Guided First‐in‐Human Studies - Matthew J. Goldstein; Malte Peters; Barbara L. Weber; Charles B. Davis (Wiley, 2021)
Many targeted therapies are administered at or near the maximum tolerated dose (MTD). With the advent of precision medicine, a larger therapeutic window is expected. Therefore, dose optimization will require a new approach to early clinical trial design. We analyzed publicly available data for 21 therapies targeting six kinases, and four poly (ADP‐ribose) polymerase inhibitors, focusing on potency and exposure to gain insight into dose selection. The free average steady‐state concentration (Css) at the approved dose was compared to the in vitro cell potency (half‐maximal inhibitory concentration (IC50)). Average steady‐state area under the plasma concentration‐time curve, the fraction unbound drug in plasma, and the cell potency were taken from the US drug labels, US and European regulatory reviews, and peer‐reviewed journal articles. The Css was remarkably similar to the IC50. The median Css/IC50 value was 1.2, and 76% of the values were within 3‐fold of unity. However, three drugs (encorafenib, erlotinib, and ribociclib) had a Css/IC50 value > 25. Seven other therapies targeting the same 3 kinases had much lower Css/IC50 values ranging from 0.5 to 4. These data suggest that these kinase inhibitors have a large therapeutic window that is not fully exploited; lower doses may be similarly efficacious with improved tolerability. We propose a revised first‐in‐human trial design in which dose cohort expansion is initiated at doses less than the MTD when there is evidence of clinical activity and Css exceeds a potency threshold. This potency‐guided approach is expected to maximize the therapeutic window thereby improving patient outcomes.